Genetic and phenotypic profile of 112 patients with X‐linked Charcot–Marie–Tooth disease type 1. (3rd August 2018) - Yuan, J.‐H.; Sakiyama, Y.; Hashiguchi, A.; Ando, M.; Okamoto, Y.; Yoshimura, A.; Higuchi, Y.; Takashima, H.
Abstract : Background and purpose: X‐linked Charcot–Marie–Tooth disease type 1 (CMTX1), caused by mutations in gap junction protein beta 1 (GJB1), is characterized by various central nervous system symptoms and gender differences of clinical severity. The aim of this study was to identify the frequency and mutation spectrum of CMTX1 patients in Japan and to demonstrate their phenotypic diversities. Methods: Using three high‐throughput sequencing systems, targeted gene panel sequencing on 1483 unrelated index patients with suspected Charcot–Marie–Tooth (CMT) disease was performed. The peripheral and central nervous system involvements of all patients with GJB1 variants were assessed retrospectively and a detailed gender comparison was conducted with the CMT examination score. Results: Twenty‐three novel and 36 described GJB1 variants were identified from 88 pedigrees, in which 34 female and 78 male patients were enrolled. Mean age at onset of the male patients was much younger than the females, 21.56 ± 17.63 years vs. 35.53 ± 23.72 years ( P = 0.007). Male patients presented with more severe phenotypes in every examination item, but statistical differences were observed only in motor dysfunctions of the lower extremities and vibration sensation. No significant sensory difference was identified between genders, either clinically or electrophysiologically. Central nervous system dysfunctions were found in 15 patients from 12 pedigrees. Therein, six patients developed stroke‐like phenotypes, with dysarthria as the leading symptom. Conclusions: A relatively lower frequency of CMTX1 (5.9%) was demonstrated and a broad mutation spectrum of GJB1 was described. Detailed clinical differences between genders and various central nervous system symptoms were also illustrated, even in the same pedigree.